Pengaruh Kompensasi dan Budaya Organisasi Terhadap Kinerja Karyawan di PT. Trimitra Sejati Jaya - Timara Oliviaputie; Ahmad Rizki Sridadi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to determine the influence of influencer marketing and social media advertisment on electronic word of mouth and customer trust, as well as the mediating role of electronic word of mouth on the influence of influencer marketing and social media advertisment on customer trust. The location of this study is in Denpasar City, Bali Province and the sample used is 150 respondents. The data analysis technique was carried out using SmartPLS 4. The results of the study show that influencer marketing has a positive and significant effect on customer trust, social media advertisment has a positive and significant effect on customer trust, influencer marketing has a positive and significant effect on electronic word of mouth, social media advertisment has a positive and significant effect on Regarding the electronic word of mouth, the electronic word of mouth has a positive and significant effect on customer trust, the role of electronic word of mouth as a mediating variable in the relationship between influencer marketing has a positive and significant influence on customer trust and the role of electronic word of mouth as a mediating variable in the relationship between Social media advertisment has a positive and significant influence on customer trust. The suggestion that can be given by the researcher is that the management of Skintific is expected to make more innovations in the product, so that later it can provide quality products, always provide direction to influencers in recommending products to consumers in order to provide accurate and reliable information, Make more interesting ads, as well as make more ads that contain product benefits, as well as testimonials from consumers who have used and are more active in promoting on social media.